2008
DOI: 10.1128/aem.01819-08
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Gibberellin Production in Fusarium verticillioides ( Gibberella fujikuroi MP-A) Is Due to a Deletion in the Gibberellic Acid Gene Cluster

Abstract: Fusarium verticillioides (Gibberella fujikuroi mating population A [MP-A]) is a widespread pathogen on maize and is well-known for producing fumonisins, mycotoxins that cause severe disease in animals and humans. The species is a member of the Gibberella fujikuroi species complex, which consists of at least 11 different biological species, termed MP-A to -K. All members of this species complex are known to produce a variety of secondary metabolites. The production of gibberellins (GAs), a group of diterpenoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…As in previous experiments with F. verticillioides [66], transformants of F. oxysporum 4287 with the F. fujikuroi GA cluster produced GAs at levels similar to those produced by F. fujikuroi IMI58289 (Table S5B). …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…As in previous experiments with F. verticillioides [66], transformants of F. oxysporum 4287 with the F. fujikuroi GA cluster produced GAs at levels similar to those produced by F. fujikuroi IMI58289 (Table S5B). …”
Section: Resultssupporting
confidence: 79%
“…However, production of GAs has only been detected in isolates of F. sacchari , F. konzum and F. proliferatum [64], [65]. In addition, the cluster is absent in the more distantly related species F. graminearum and F. solani [66]. Here, analysis of genome sequences revealed that homologues of the entire F. fujikuroi GA cluster are present in F. circinatum , F. mangiferae , and five isolates of F. oxysporum (Figure 4).…”
Section: Resultsmentioning
confidence: 87%
“…Consistent with findings in other fungi, we found 11 secondary metabolite genes exclusively downregulated at 120 h. These include Fffum1 and Fffum2 , encoding a polyketide synthase and P450 monooxygenase respectively, required for fumonisin production (Proctor et al ., 2003) and des , required for GA synthesis (Tudzynski et al ., 2003). des is the only gene of the F. fujikuroi GA cluster present in F. verticillioides (Bömke et al ., 2008) (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…CcsD exhibits similarity to GliF from A. fumigatus (42 % protein identity) that possibly catalyzes the formation of an arene oxide in gliotoxin biosynthesis (Gardiner and Howlett, 2005); hence, CcsD may be responsible for the epoxidation of the C6-C7 double bond. The closest characterized homolog of CcsG is GA-P450-4 (39% identity) from Gibberella moniliformis , which is an ent -kaurene oxidase that catalyzes the multiple oxidations of ent -kaurene to ent -kaurenoic acid (Bomke et al, 2008). This hints that CcsG may be responsible for the successive oxidative modifications at C17 and C18.…”
Section: Resultsmentioning
confidence: 99%